MANAGEMENT AND RECONCILIATION ANTHROPOGENIC ACTIONS WITH THE REGIME OF NATURE MANAGEMENT IN THE CATTLE-BREEDING COMPLEX - Chmil, A. (Енергетика і автоматика, 2016)
The structure and composition of the information flow matching system of human action environment with modes of nature. It is proposed to diagnose the state of environmental objects based on the ratio of environmental safety.